Estimated glomerular filtration rate in apparently healthy term neonates in Nigeria - Madise-Wobo, Akpoembele Deborah; Disu, Elizabeth Aruma; Gbelee, Olusegun Henry; Solarin, Adaobi; Animasahun, Barakat Adeola (African Journal of Nephrology, 2018)
Background: Glomerular filtration rate (GFR) is the best measure of renal function. However, the ideal exogenous markers are not routinely used to estimate GFR in clinical settings. Outside Africa, GFR estimates for neonates have been calculated from formulae using creatinine as well as cystatin C. There is a paucity of data on estimated GFR in neonates in Africa. This study was conducted to estimate GFR in healthy term African neonates using cystatin C-based equations. Methods: One hundred and thirteen apparently healthy term babies with normal Apgar scores were recruited at birth. Cystatin C was measured in cord blood at birth and in venous samples from neonates on the third day of life. GFR was estimated using the Filler and Lepage as well as the Zappitelli et al. cystatin C-based equations. These estimates were compared with a reference GFR estimate of 41 ± 15 mL/min/1.73 m2. Results: The median (interquartile range) estimated GFR values based on cord blood and day 3 venous samples using the Filler and Lepage equation were 44.67 (36.35–72.44) and 51.29 (38.90–72.44) mL/min/1.73 m2, respectively. When the Zappitelli equation was applied, the estimates were 38.18 (31.84–61.34) and 43.82 (33.75–61.34) mL/min/1.73 m2, respectively. The GFR estimates derived from both equations did not differ in respect of the gestational age, sex and postnatal ages of the babies. Conclusions: GFR estimates using the Zappitelli equation had values that were closely related to reference GFR measures for neonates whereas the GFR estimates using the Filler and Lepage equation had higher values.